The Relationship of Emotional Intelligence, Learning Independence and Learning Motivation with Learning Outcomes - Hasnidah Mulyadi; Firdaus Daud; Hartono Hartono; Yusminah Hala (Jurnal Penelitian Pendidikan IPA, 2025)
One of the common issues in the learning process is the low learning outcomes of students, which can be caused by various factors, including low emotional intelligence, learning independence, and learning motivation. This study aims to determine the relationship between emotional intelligence, learning independence, and learning motivation with the science learning outcomes of eighth-grade students at public junior high schools in Panca Rijang Subdistrict, Sidrap Regency. This is a quantitative study using a correlational approach. The study population consists of all eighth-grade students from four public junior high schools, with a sample size of 153 participants selected using simple random sampling. The research instruments include a Likert scale questionnaire to measure emotional intelligence, learning independence, and learning motivation, as well as a multiple-choice test to assess science learning outcomes. The data analysis technique used was path analysis with the assistance of SPSS 25.0. The results of the study showed a significant direct relationship between emotional intelligence, learning independence, and learning motivation with science learning outcomes. Additionally, learning motivation was found to act as an intervening variable that partially mediated the relationship between emotional intelligence and learning independence on science learning outcomes. In conclusion, strengthening emotional intelligence, enhancing learning independence, and developing learning motivation simultaneously can positively contribute to improving students' science learning outcomes. Therefore, a holistic and character-development-oriented learning approach is needed.